Energy Requirements in Early Life Are Similar for Male and Female Goat Kids - Bompadre, T. F. V. [UNESP]; Boaventura Neto, O. [UNESP]; Mendonca, A. N. [UNESP]; Souza, S. F. [UNESP]; Oliveira, D. [UNESP]; Fernandes, M. H. M. R. [UNESP]; Harter, C. J. [UNESP]; Almeida, A. K. [UNESP]; Resende, K. T. [UNESP]; Teixeira, I. A. M. A. [UNESP] (Asian-australasian Assoc Animal Production Soc, 2014)
Little is known about the gender differences in energetic requirements of goats in early life. In this study, we determined the energy requirements for maintenance and gain in intact male, castrated male and female Saanen goat kids using the comparative slaughter technique and provide new data on their body composition and energy efficiency. To determine the energy requirements for maintenance, we studied 21 intact males, 15 castrated males and 18 females (5.0 +/- 0.1 kg initial body weight (BW) and 23 +/- 5 d of age) using a split-plot design with the following main factors: three genders (intact males, castrated males, and females) and three dry matter intake levels (ad libitum, 75% and 50% of ad libitum intake). A slanghter group included three kids, one for each nutritional plane, of each gender, and all three animals within a group were slaughtered when the ad libitum kid reached 15 kg in BW. Net energy requirements for gain were obtained for 17 intact males, eight castrated males and 15 females (5.1 +/- 0.4 kg BW and 23 +/- 13 d of age). Animals were fed ad libitum and slaughtered when they reached 5, 10, and 15 kg in BW. A digestion trial was performed with nine kids of each gender to determine digestible energy, metabolizable energy and energy metabolizability of the diet. Our results show no effect of gender on the energy requirements for maintenance and gain, and overall net energy for maintenance was 205.6 kJ/kg(0.75) empty body weight gain (EBW) (170.3 kJ/kg(0.75) BW) from 5 to 15 kg BW. Metabolizable energy for maintenance was calculated by iteration, assuming heat production equal to metabolizable energy intake at maintenance, and the result was 294.34 kJ/kg(0.75) EBW and k(m) of 0.70. As BW increased from 5 to 15 kg for all genders, the net energy required for gain increased from 9.5 to 12.0 kJ/g EBW gain (EWG), and assuming k(g) = 0.47, metabolizable energy for gain ranged from 20.2 to 25.5 kJ/g EWG. Our results indicate that it is not necessary to formulate diets with different energetic content for intact male, castrated male and female Saanen goat kids weighing from 5 to 15 kg.
Keywords: Body Composition; Comparative Slaughter; Gender; Growth; Intake; Metabolism